2018
DOI: 10.1021/acs.est.8b00569
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Effects and Demographic Responses of Zebrafish (Danio rerio) Exposed to Organo-Bromine Compounds

Abstract: Long-term exposure to toxic chemicals often has deleterious effects on aquatic organisms. In order to support appropriate environmental management of chemicals, a mathematical model was developed to characterize the effects of chemicals on multigenerational population dynamics in aquatic animals. To parametrize the model, we conducted a multigenerational laboratory toxicity test in zebrafish ( Danio rerio) exposed to 2-bromo-4,6-dinitroaniline (BDNA). Long-term exposure to BDNA considerably reduced the fecundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Previous studies have reported the mutagenicity and reproductive toxicities of brominated azo dyes, ,,, and it is likely that chlorinated azo dyes follow similar toxicity pathways. Thus, chlorinated azo dyes are of concern, given their higher abundances than brominated analogues.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have reported the mutagenicity and reproductive toxicities of brominated azo dyes, ,,, and it is likely that chlorinated azo dyes follow similar toxicity pathways. Thus, chlorinated azo dyes are of concern, given their higher abundances than brominated analogues.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, the mutagenicity of BDNA has been reported with the Ames (TA98) assay at a relatively low concentration (1.25 μg/mL) . In vivo aquatic toxicities of BDNA also revealed its impacts on zebrafish reproductivity and development after long-term exposure to BDNA at a concentration as low as 0.5 μg/L. , Thus, investigation of the potential bioactivation of BADs, for instance, to produce BDNA is critical to understand their potential adverse effects.…”
Section: Introductionmentioning
confidence: 99%